Age, growth, reproductive biology and mortality of Cranoglanis multiradiatus, a threatened freshwater fish in Hainan Island, China. (21st December 2021) - Liu, Fei; Yongo, Edwine; Liang, Zhice; Fu, Qiongyao; Huang, Bo; Cai, Xing Wei; Guo, Zhiqiang
Abstract: Age, growth, reproductive biology and mortality of Cranoglanis multiradiatus were studied in the present study. A total of 731 specimens were collected monthly using the benthic fyke nets and gillnets from October 2019 to September 2020 in Nandu River. Sagittal otolith was used for age determination, and the maximum age for both female and male was estimated to be 5 years. Female and male C . multiradiatus showed different growth pattern, which was expressed as Lt  = 304.48 × (1 +  e −0.39 ( t  + 0.30) ) −1 and Lt  = 273.31 × (1 +  e −0.60 ( t  + 0.29) ) −1, respectively. The overall sex ratio was 1: 0.56 (male: female). Female attained sex maturity at 3 years (239.00 mm body length). Month variation of gonad‐somatic index indicated that the spawning period occurred from April to September. The absolute fecundity was estimated at 2545 ± 1482 eggs per ind. and the relative fecundity was 16.18 ± 9.39 per g. The fishing mortality was 1.05, and the exploitation rate was 0.66, which indicated C . multiradiatus was very likely under overfishing. This study provided data on the key life history traits of C . multiradiatus, which has been not known previously and is essential for conservation strategy and policy development.